IUPHAR-review: The integration of classic psychedelics into current substance use disorder treatment models - David B. Yaden; Andrea P. Berghella; Peter S. Hendricks; Mary E. Yaden; Michael Levine; Julia S. Rohde; Sandeep Nayak; Matthew W. Johnson; Albert Garcia-Romeu (Elsevier, 2024)
Substance use disorders (SUDs) have an enormous impact on public health. With classic psychedelic-assisted therapies showing initial promise in treating multiple SUDs, it is possible that these treatments will become legally available options for patients with SUDs in the future. This article highlights how classic psychedelic-assisted therapies might be integrated into current clinical practice. We first describe contemporary evidence-based treatments for SUDs and highlight how classic psychedelic-assisted therapies might fit within each treatment. We suggest that classic psychedelic-assisted therapies can be integrated into most mainstream evidence-based SUD treatments that are currently used in clinical settings, indicating broad compatibility of classic psychedelics with contemporary SUD treatment paradigms.